Future Circular Collider: Integrated Programme and Feasibility Study - Benedikt, Michael; Zimmermann, Frank (Frontiers in Physics, 2022)
The Future Circular Collider (FCC) Integrated Project foresees, in a first stage, a high-luminosity high-energy electron-positron collider, serving as Higgs, top and electroweak factory, and, in a second stage, an energy frontier hadron collider, with a centre-of-mass energy of at least 100 TeV. This programme well matches the highest priority future requests issued by the 2020 Update of the European Strategy for Particle Physics. In 2021, with the support of the CERN Council, a five-year FCC Feasibility Study was launched. In this article, we present the FCC integrated project and the preparations for the FCC Feasibility Study.